Damping oscillations in a wire bending process. (October 2022) - Baraldo, Andrea; Bascetta, Luca; Caprotti, Fabrizio; Ferretti, Gianni; Ponti, Angelo; Sakcak, Basak
Abstract: This paper presents an approach to modify CAD/CAM generated motion profiles for wire bending machines, in order to damp wire oscillations without decreasing machine throughput. Two different methodologies are presented, both leveraging on a simple and easily identifiable model of wire oscillations, the first one based on a filtering approach, the second one on an optimisation approach. The two methodologies are both characterised by a low computational complexity, allowing them to be integrated directly in the bending machine user interface, and can rely on a standard camera to identify wire oscillation parameters. A thorough experimental validation of the approaches is also presented, showing promising results in damping oscillations with wires of different materials. Highlights: Oscillations increase settling time in machining operations, decreasing throughput. A simple and easily identifiable model of wire oscillations is considered. Filtering and optimisation approach to generate oscillation-free motion profiles. Both methodologies are characterised by a low computational complexity. Both methodologies rely on a standard camera to identify wire oscillation model.